The influence of debt to assets ratio (DAR), inventory turnover (ITO), total assets turnover (TATO), net profit margin (NPM), and sales growth (SG) on return on assets (ROA) at PT Sritex TBK period 2013-2022 - Sonia Chandra Utami; Yoyo Sudaryo; Gurawan Dayona Ismail; Riyandi Nur Sumawidjaja; Andre Suryaningprang; Dadan Abdul Aziz (Sean Institute, 2024)
This research was conducted to determine the effect of Debt to Assets Ratio (DAR), Inventory Turnover (ITO), Total Assets Turnover (TATO), Net Profit Margin (NPM) and Sales Growth on PT Sritex's Return On Assets (ROA) for the 2013-2022 period. The research method used uses quantitative research methods with descriptive and verification approaches. The data source in this research is secondary data obtained through annual financial reports using purposive sampling techniques. Data analysis techniques use descriptive analysis techniques, verification analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing, both partial and simultaneous testing with data analysis tools using SPSS version 25. The results of this research partially show Inventory Turnover (ITO), Total Assets Turnover (TATO) and Net Profit Margin (NPM) have a significant effect on Return On Assets (ROA), while Debt to Assets Ratio (DAR) and Sales Growth have no significant effect on Return On Assets (ROA), while simultaneously all independent variables has a significant effect on Return On Assets (ROA).